The Relationship Between Human Resource Management Practices and Employee Performance - Lim, Chuan Terng; Ahmad, Nurazwa (Research in Management of Technology and Business, 2021)
As Malaysia is gradually becoming a developed country, the country should pay more attention to the development of the services industry as a machine to promote and sustain economic growth. Based on the Eleventh Malaysia Plan, 2016-2020, the services industry will continue to be a key driver of economic growth. There is lack of studies been conducted on the relationship between Human Resource Management (HRM) practices and employee performance from Malaysia perspective in past researches. The objective of this study is to determine the level of employee performance, to determine the level of HRM practices and to investigate the relationship between the HRM practice and employee performance. A survey among 245 employees from banking service sector in Johor, Malaysia had been conducted. Quantitative approach had been used in this study and data collection was using questionnaire and online distribution. The data were analyzed using four analyses which are descriptive analysis, reliability analysis, normality test and correlation analysis. The results showed that the level of employee performance and the level of HRM practices was high and there was a positive relationship between HRM practices and employee performance. The findings in this study will help managers to determine the best combination of HRM practices which include training and development, compensation and benefits, performance appraisals and work-life policies and help to improve employee performance by developing effective strategies for these practices.